2017
DOI: 10.1016/j.ultsonch.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (5.0%)Er3+:Y3Al5O12/Pt-(TiO2-Ta2O5) nanocatalysts and application in sonocatalytic decomposition of ametryn in aqueous solution

Abstract: (5.0%)Er:YAlO/Pt-(TiO-TaO) powder, as a high effective sonocatalyst, was prepared using sol-gel and calcination method. Then it was characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). In order to evaluate the sonocatalytic activity of the prepared (5.0%)Er:YAlO/Pt-(TiO-TaO) powder, the sonocatalytic decomposition of ametryn was studied. In addition, some influencing factors such as different Ti/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…As shown in Fig. (a), some typical XRD diffraction peaks at 2θ = 18.15° (211), 33.50° (400), 41.50° (422), 46.62° (521) and 55.12° (532) are found, which are the same as previously reported, belonging to the characteristic diffraction peaks of Er 3+ :Y 3 Al 5 O 12 . According to the characteristic diffraction peaks of 28.32° and 36.75° in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. (a), some typical XRD diffraction peaks at 2θ = 18.15° (211), 33.50° (400), 41.50° (422), 46.62° (521) and 55.12° (532) are found, which are the same as previously reported, belonging to the characteristic diffraction peaks of Er 3+ :Y 3 Al 5 O 12 . According to the characteristic diffraction peaks of 28.32° and 36.75° in Fig.…”
Section: Resultssupporting
confidence: 86%
“…First, Er 3+ :Y 3 Al 5 O 12 was prepared by the sol–gel and calcination method (for more details refer to a previous report). P‐TET as sonocatalyst was prepared in the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it is utmost importance to identify the main active species and determine their roles in the formation of intermediates in order to develop and understand the mechanisms underlying the reactivity of photocatalysts for environmental remediation [39]. Although some studies of ametryn degradation by photocatalysis have been reported [40][41][42][43][44][45], none of them investigated the role of reactive species involved in the degradation process and their role in the degradation pathways. This work focused on the elucidation of the photocatalytic mechanism for the removal of ametryn by TiO2 catalysts under simulated solar light.…”
Section: Introductionmentioning
confidence: 99%